A randomised controlled trial evaluating the use of enteral nutritional supplements postoperatively in malnourished surgical patients. Issue 6 (1st June 2000) - Beattie, A H; Prach, A T; Baxter, J P; Pennington, C R
Abstract : BACKGROUND: Patients who undergo surgery are at risk of malnutrition due to periods of starvation, the stress of surgery, and subsequent increase in metabolic rate. There are limited data on nutritional outcome of surgical patients. AIMS: To investigate changes in nutritional status and the influence of oral supplements on nutritional status, morbidity, and quality of life in postoperative surgical patients. METHODS: Entry was determined by the presence of malnutrition, as defined by a body mass index (BMI) ⩽20 kg/m 2, anthropometric measurements ⩽15th percentile on admission, or initiation of oral diet postoperatively and/or a weight loss of 5% or more during the operative period. We studied 101 patients: 52 were randomised to the treatment group (TG) and prescribed a 1.5 kcal/ml nutritional supplement; 49 patients were randomised to the control group (CG) and continued with routine nutritional management. Nutritional status was assessed by weight, anthropometry, and grip strength, with measurements taken at two weekly intervals for 10 weeks. Complications, namely wound infection, chest infection, and antibiotic use were documented. Quality of life (QOL) was assessed using the UK SF-36 questionnaire. RESULTS: Patients in the control group lost a maximum mean (SD) of 5.96 (4.21) kg in weight over a period of eight weeks while patients in group TG lost less weight overall (maximum mean (SD) 3.40 (0.89) kg (p<0.001) occurring at four weeks and progressively regained weight from week 4). Anthropometry, grip strength, and QOL were similarly significantly different between groups (p<0.001). Fewer patients in the treatment group (7/52) required antibiotic prescriptions compared with the control group (15/49). CONCLUSIONS: Nutritional status declined for two months after discharge. Postoperative nutritional supplementation improved nutritional status, QOL, and morbidity in these patients.